ANALISIS INTEGRASI PASAR BAWANG MERAH MENGGUNAKAN METODE VECTOR ERROR CORRECTION MODEL (VECM) (Studi Kasus: Harga Bawang Merah di Provinsi Jawa Tengah) - Rizky Aditya Akbar; Agus Rusgiyono; Tarno Tarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Spatial market integration is the degree of closeness of relationship between the regional market with other regional market. Vertical market integration is the level of the relationship between a marketing agency with other marketing agencies in the marketing. Spatial market integration in onion prices at the wholesale level for the area of Brebes, Tegal, Pemalang, Semarang, Salatiga, Surakarta and can be analyzed using the Vector Error Correction Model (VECM) to see where the long-term relationship. Vertical market integration in onion prices in the wholesale and consumer levels for Tegal, Semarang and Surakarta can be analyzed using the Granger Causality. The data used are the monthly time series data from January 2010 until February 2016, where data must be stationary at the first difference. Based on Johansen cointegration test obtained their long-term relationship at all six of the region and can be used to analyze VECM method. Granger Causality used as a test of causality. From this study, it can be concluded the onion market in Central Java is not fully integrated spatial whereby if shocks in Brebes then be transmitted to the market in Pemalang, Semarang, Salatiga and Surakarta whereas if shocks occur in Tegal will be transmitted to Semarang, Salatiga and Surakarta. This occurs because Brebes as the central region producing onion and Tegal as many areas in need of onion. The existence of vertical integration only occurs in Semarang, although only one-way causality. Keywords: Market Integration, Johansen Cointegration Test, VECM, Granger Causality Test.